The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.chroma.2019.460788
|View full text |Cite
|
Sign up to set email alerts
|

Halogen bond in separation science: A critical analysis across experimental and theoretical results

Abstract: The halogen bond (XB) is a noncovalent interaction involving a halogen acting as electrophile and a Lewis base. In the last decades XB has found practical application in several fields. Nevertheless, despite the pivotal role of noncovalent interactions in separation science, investigations of XB in this field are still in their infancy, and so far a limited number of studies focusing on solid phase extraction, liquid-liquid microextraction, liquid-phase chromatography, and gas chromatography separation have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 80 publications
(124 reference statements)
1
44
0
Order By: Relevance
“…Moreover, in principle, halogens can also act as HB acceptors through the electron density located on the belt around the σ-hole region (Fig. 3b) [6]. Nevertheless, in compounds 1-7, other more negative regions are present with better capability as HB acceptors.…”
Section: Analyte Structuresmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, in principle, halogens can also act as HB acceptors through the electron density located on the belt around the σ-hole region (Fig. 3b) [6]. Nevertheless, in compounds 1-7, other more negative regions are present with better capability as HB acceptors.…”
Section: Analyte Structuresmentioning
confidence: 99%
“…XB is a noncovalent interaction occurring between a Lewis base (XB acceptor) and an electropositive region (the so-called σ-hole) located on bound halogens (XB donors) [31]. In our previous studies, we demonstrated by chromatographic and computational analyses that the carbonyl oxygens of Amy-3,5-diMe and cellulose-3,5-diMe are able as Lewis bases to form XBs with the electrophilic σ-hole regions of halogen substituents (XB donors) bound to the 4,4'-bipyridine rings [6,20,26]. Moreover, in principle, halogens can also act as HB acceptors through the electron density located on the belt around the σ-hole region (Fig.…”
Section: Analyte Structuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with SBE and SBE/C before Eosin Y adsorption, the FTIR peaks of SBE and SBE/C after Eosin Y adsorption decreased or disappeared at 1,705, 1,630, 1,034, 2,923, and 2,854 cm −1 (Figure ), which was caused by the adsorption of Eosin Y. It is worth noting that Eosin Y and two adsorbents both have oxygenated functional groups and aromatic rings, and Eosin Y also contains C‐Br bond, which creates the conditions for hydrogen bonding (Huang, Bin, Bu, Jiang, & Zeng, 2011), halogen bonding (Peluso et al., 2019), and π‐π interaction (Wan et al., 2019). The view was also supported by FTIR spectrum.…”
Section: Resultsmentioning
confidence: 96%